2020
DOI: 10.3390/w12020600
|View full text |Cite
|
Sign up to set email alerts
|

Using a Data Driven Approach to Predict Waves Generated by Gravity Driven Mass Flows

Abstract: When colossal gravity-driven mass flows enter a body of water, they may generate waves which can have destructive consequences on coastal areas. A number of empirical equations in the form of power functions of several dimensionless groups have been developed to predict wave characteristics. However, in some complex cases (for instance, when the mass striking the water is made up of varied slide materials), fitting an empirical equation with a fixed form to the experimental data may be problematic. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
2
10
0
2
Order By: Relevance
“…As with Islam et al [ 42 ], we observed that the hydrogels based on Carbopol ® Ultrez TM 10 and 30 were shear-thinning fluids characterized by a low degree of thixotropy and the presence of yield stress ( Figure 5 ). The flow curves with increasing and decreasing shear rates were best described by the Herschel–Bulkley model, which was also confirmed by Meng et al [ 25 , 62 ]. At T = 25 °C, the curves were very close to each other, whereas at T = 32 °C, the hysteresis area increased slightly (H1-INS 10.66 Pa/s vs. 16.68 Pa/s; H2-INS 31.40 Pa/s vs. 39.09 Pa/s).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As with Islam et al [ 42 ], we observed that the hydrogels based on Carbopol ® Ultrez TM 10 and 30 were shear-thinning fluids characterized by a low degree of thixotropy and the presence of yield stress ( Figure 5 ). The flow curves with increasing and decreasing shear rates were best described by the Herschel–Bulkley model, which was also confirmed by Meng et al [ 25 , 62 ]. At T = 25 °C, the curves were very close to each other, whereas at T = 32 °C, the hysteresis area increased slightly (H1-INS 10.66 Pa/s vs. 16.68 Pa/s; H2-INS 31.40 Pa/s vs. 39.09 Pa/s).…”
Section: Discussionsupporting
confidence: 82%
“…As with Islam et al [42], we observed that the hydrogels based on Carbopol ® Ultrez TM 10 and 30 were shear-thinning fluids characterized by a low degree of thixotropy and the presence of yield stress (Figure 5). The flow curves with increasing and decreasing shear rates were best described by the Herschel-Bulkley model, which was also confirmed by Meng et al [25,62]. At T = 25 • C, the curves were very close to each other, whereas at T = 32 Low yield stress values of the H1-INS formulation suggest a lighter texture, easier melting of the hydrogel on the skin surface, and a higher insulin diffusion coefficient at the application site, which was confirmed in the pharmaceutical availability study.…”
Section: Discussionsupporting
confidence: 80%
“…with a regression analysis. In addition, ANNs were previously successfully used for solving similar coastal engineering problems (Baldock et al, 2019;van Gent et al, 2007;Meng et al, 2020;Panizzo and Briganti, 2007;Panizzo et al, 2005;Pourzangbar et al, 2017, amongst others).…”
Section: The Effect Of the Bathymetry On Landslide-tsunami Propagationmentioning
confidence: 99%
“…The HST model is one of the most acknowledged statistical models, which describes the settlement as a combination of hydro-statistic components, temperature components, and aging components. With the development of computer science, plenty of machine learning-based methods have been applied to predict the settlement of CFRDs [12,13]. Owing to the strong ability to map the nonlinear relationship between the settlement and its explanatory variables, the machine learning techniques improve the performance of the prediction model intensely.…”
Section: Introductionmentioning
confidence: 99%